Procurement Challenges in Universities: A Snapshot and Legal Reform Approaches to Resolution - Fibrianti, Nurul; Rahayu, Sang Ayu Putu; Fidiyani, Rini; Putra, Tegar Islami; Prasetya, Rizky Andeza (Journal of Law and Legal Reform, 2025)
Procurement is not limited to the scope of goods but also extends to services. Therefore, it is essential to both quality goods and services. However, it cannot be denied that universities face various obstacles in terms of procuring goods and services, leading to several challenges. The problems addressed in this research are: (1) What are the issues faced in the procurement of goods and services at universities? (2) What is the problem-solving model for procurement of goods and services at universities? This research utilizes a qualitative approach, with a sociological juridical research method, or non-doctrinal research.